Surface finishing of flat pieces when submitted to lapping kinematics on abrasive disc dressed under several overlap factors - Sanchez, L. E. A. [UNESP]; Jun, N. Z. X. [UNESP]; Fiocchi, A. A. [UNESP] (Elsevier B.V., 2011)
In machining of pieces that require surface finishing levels finer than grinding can offer, it is necessary to use specific finishing processes. However, these processes, which have lapping as the most classic representative, are usually difficult to setup and demand much time in setting the large number of variables. This paper discusses the investigation of an abrasive process for finishing of flat workpieces based on the combination of important grinding and lapping characteristics. Instead of loosing abrasive grains between the workpiece and the lapping plate, a resinoid grinding wheel of hot-pressed silicon carbide is fixed on the plate of a device resembling to a lapping machine. The grinding wheel is dressed with a single-point diamond for maintaining its form flat and mainly for interfering in the workpieces surface finishing by varying of the overlap factor (Ud). It was noticed that the studied process can simplify the setup and make it easier than in lapping, which is a painstaking process. The surface roughness values and flatness deviations showed to be comparable to those achieved in lapping, or even better. The best surface roughness and flatness deviation found were Ra = 0.8 nm and 0.4 mu m with Ud = 3, respectively. The workpiece material was made of quenched and tempered SAE 4340 steel, reaching a hardness of 60 HRC. The process was also monitored by acoustic emission (AE), which indicates to be a promising and suitable technique to housed in this process. Compared to lapping, there is an additional advantage of a less contaminated workpiece surface with a shiny appearance. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Overlap factor; Lapping; Grinding; Surface roughness; Flatness